INNOVATION IN THE ORGANIZATION OF TECHNOLOGY LESSONS THE IMPORTANCE OF USING TECHNOLOGY (American Journal of Interdisciplinary Research and Development, 2025)
It was introduced in many countries of the world as the most acceptable form of education during the pandemic. However, many studies prove that it is not as effective as traditional education. Therefore, we have conducted research to identify learning strategies that can be effective in providing online training. The empirical basis of the article is a survey conducted among students and teachers, and the methodological basis is scientific articles published in authoritative journals on the subject.